Performance of orientation distribution function‐fingerprinting with a biophysical multicompartment diffusion model. Issue 1 (28th February 2022) - Filipiak, Patryk; Shepherd, Timothy; Lin, Ying‐Chia; Placantonakis, Dimitris G.; Boada, Fernando E.; Baete, Steven H.
Abstract : Purpose: Orientation Distribution Function (ODF) peak finding methods typically fail to reconstruct fibers crossing at shallow angles below 40°, leading to errors in tractography. ODF‐Fingerprinting (ODF‐FP) with the biophysical multicompartment diffusion model allows for breaking this barrier. Methods: A randomized mechanism to generate a multidimensional ODF‐dictionary that covers biologically plausible ranges of intra‐ and extra‐axonal diffusivities and fraction volumes is introduced. This enables ODF‐FP to address the high variability of brain tissue. The performance of the proposed approach is evaluated on both numerical simulations and a reconstruction of major fascicles from high‐ and low‐resolution in vivo diffusion images. Results: ODF‐FP with the suggested modifications correctly identifies fibers crossing at angles as shallow as 10 degrees in the simulated data. In vivo, our approach reaches 56% of true positives in determining fiber directions, resulting in visibly more accurate reconstruction of pyramidal tracts, arcuate fasciculus, and optic radiations than the state‐of‐the‐art techniques. Moreover, the estimated diffusivity values and fraction volumes in corpus callosum conform with the values reported in the literature. Conclusion: The modified ODF‐FP outperforms commonly used fiber reconstruction methods at shallow angles, which improves deterministic tractography outcomes of major fascicles. In addition, the proposed approach allows for linearization of the microstructure parameters fitting problem.